Study on the alkaloids of Anona squamosa Linne (Family Anonaceae) - Talain, Estrella C.; Santos, Rizalina B.; Concepcion. Adoracion B. (Quezon City: College of Pharmacy, University of the Philippines, 1980.)
The alkaloids of Anona squamosa Linne (Family Anonaceae) was studied using different methods which were learned in our previous pharmacy and chemistry courses. Among the techniques employed were melting point determination, thin-layer chromatography and spectrophotometric techniques of analysis.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, March 1980.
Keywords: Annonaceae; Atis